TECHNOLOGY-ENHANCED LEARNING (TEL) IN TEACHING MATHEMATICS AT LYCEUMS - Abdullayeva Muborak Rahmatullayevna (Journals Park Publishing, 2023)
Technology-Enhanced Learning (TEL) in mathematics refers to the integration of technology tools and resources to enhance the teaching and learning of mathematics. It involves leveraging digital platforms, software applications, online resources, and interactive tools to support mathematical instruction, practice, and exploration.
Keywords: collaboration, online platforms, communication tools, virtual environments, mathematical problem-solving, mathematical investigations, mathematics research projects.